Design and Build Automatic Transfer Switch (ATS) Based Internet of Things on Microgrid System - Andhika Rizkita Putera; Muhammad Nizam; Feri Adriyanto (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
Electrical energy is a primary human requirement for continuously operating electronic devices. However, nonrenewable electrical energy is becoming increasingly scarce. As a backup power source, regenerative energy sources are an option. Because the conventional power grid transfer system takes a relatively long time, the application of a control system on the power grid transfer automatically can maximize efficiency, safety, and accuracy. In this study, an ATS system was developed using the electrical grid switching method for 300ms, 600ms, and 1000ms, as well as IoT to optimize the ATS manual override system with monitor voltage, current, and power. The test results show that the switching accuracy of 300ms is 98.40% and 98.18% with an average voltage of 19.65V and 41.22V when switching, 600ms switching is 98.14% and 99.25% with an average voltage of 17.77V and 18.18V when switching, and 1000ms switching is 99.40% and 99.41% with an average voltage of 17.52V and 21.05V, respectively. The voltage overshoot is obtained for 16ms and 40ms in linear loading and is stable within 2ms. There is harmonic distortion when loading non-linear for 9 cycles and 2 cycles of periodic frequency. The hardware data transmission accuracy is 97.94%, and the success rate of manual override is 100%.